Titanium base surface chlorine-resistant conductive and corrosion-resistant composite coating and preparation method thereof

CN122879680APending Publication Date: 2026-10-09SHENZHEN IRETRON TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611370507.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-04
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0002]铱钽氧化物涂层和钌铱钽三元氧化物涂层是较为常见的活性涂层体系,此类涂层电极在含氯离子的电化学环境中使用时,阳极表面发生的析氯反应及随后生成的强氧化性物种会对氧化物涂层造成不可逆侵蚀,导致涂层逐渐剥落、活性下降,缩短涂层电极的使用寿命

Benefits of technology

通过设置聚苯并二呋喃二酮导电聚合物表面层,有效阻挡溶液中的有机添加剂分子向钌铱钽三元氧化物中间层表面迁移和氧化,降低有机添加剂在阳极上的无效消耗,有助于维持溶液成分稳定、降低生产成本。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122879680A_ABST
    Figure CN122879680A_ABST
Patent Text Reader

Abstract

The application provides a titanium substrate surface chlorine-resistant conductive corrosion-resistant composite coating and a preparation method thereof. The titanium substrate is pretreated, a ruthenium-iridium-tantalum ternary oxide intermediate layer is prepared on the surface of the titanium substrate, an alcohol solution of polybenzodifuranone is coated on the surface of the intermediate layer, and then drying and low-temperature solidification are performed to form a polybenzodifuranone conductive polymer surface layer with a thickness of 200-2000 nm, so that the titanium substrate surface chlorine-resistant conductive corrosion-resistant composite coating is obtained. The composite coating can effectively block the molecules of electroplating additives from reaching the anode active surface, delays the oxidation and consumption of the additives, the protection layer does not affect the electrocatalytic activity of the anode, the service life of the coating in the chlorine-containing environment can be prolonged, and the preparation method is simple and compatible with the existing anode production process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electrode material coating technology, and in particular to a chlorine-resistant, conductive, and corrosion-resistant composite coating for a titanium substrate and its preparation method. Background Technology

[0002] Iridium-tantalum oxide coatings and ruthenium-iridium-tantalum ternary oxide coatings are common active coating systems. When these coated electrodes are used in an electrochemical environment containing chloride ions, the chloride evolution reaction on the anode surface and the subsequent generation of strong oxidizing species cause irreversible corrosion to the oxide coating, leading to gradual peeling, decreased activity, and a shortened lifespan of the coated electrode. Meanwhile, in actual electrochemical processes, the solution usually contains a certain amount of organic additives. These organic additive molecules are prone to oxidation side reactions on the anode surface, resulting in ineffective consumption of the additives, increasing production costs and affecting the stability of the solution composition.

[0003] To address the lifespan issue of titanium-based oxide coated electrodes in chlorine-containing environments, existing technologies have proposed various improvement methods. For example, adding an intermediate layer between the titanium substrate and the active coating can improve the coating's adhesion and corrosion resistance. However, this method requires significant equipment investment and is difficult to scale up on conventional electrode coating production lines. Alternatively, adjusting the sandblasting and acid etching processes of the titanium substrate can increase surface roughness. While this can extend the coating lifespan to some extent, the process parameters are sensitive to the final result, batch consistency is difficult to control, and excessive roughening can easily lead to uneven coating thickness and localized current concentration.

[0004] Existing solutions mostly use p-type conductive polymers such as polyaniline and polypyrrole to prevent chloride ions or oxidizing species from penetrating into the coating. However, these materials have insufficient long-term stability in high anodic potential and strong oxidizing chlorine-containing environments and are prone to oxidative degradation.

[0005] Therefore, in the field of metal substrate surface coating technology, there is an urgent need for a composite coating and its preparation method that can improve the corrosion resistance life of titanium oxide coated electrodes in chlorine-containing environments, reduce the ineffective consumption of organic additives on the anode, and have a simple preparation process suitable for large-scale production. Summary of the Invention

[0006] The main objective of this invention is to provide a chlorine-resistant, conductive, and corrosion-resistant composite coating for a titanium substrate and its preparation method. By constructing a low-temperature curing polybenzodifuran diketone protective layer on the surface of the iridium tantalum oxide active layer, the electroplating additive molecules are effectively blocked from reaching the anodic active surface, significantly delaying the oxidation consumption of the additives.

[0007] To achieve the above objectives, the present invention provides a method for preparing a chlorine-resistant, conductive, and corrosion-resistant composite coating on a titanium substrate surface, comprising the following steps: The surface of the titanium substrate is first roughened by sandblasting, then etched with oxalic acid, cleaned and dried for later use. A soluble precursor salt containing ruthenium, iridium, and tantalum is dissolved in an alcohol solvent to obtain a coating solution. The coating solution is then applied to the surface of the titanium substrate. After each coating, the substrate is pre-baked at 130–160°C and then sintered at 550–600°C. This coating, pre-baking, and sintering process is repeated 8–16 times to form a ruthenium-iridium-tantalum ternary oxide intermediate layer with a thickness of 5–10 μm on the surface. The molar ratio of ruthenium, iridium, and tantalum in the soluble precursor salt is (1–5):(1–5):(5–9). Polybenzodifuran dione was dissolved in a mixed solvent containing ethanol and dimethyl sulfoxide to obtain a polymer coating solution; The polymer coating liquid is applied to the surface of the ruthenium-iridium-tantalum ternary oxide intermediate layer. The solvent is first removed by drying at 80-120°C, and then cured into a film at 160-300°C. After cooling, a polybenzodifuran diketone conductive polymer surface layer with a thickness of 200-2000 nm is formed on the ruthenium-iridium-tantalum ternary oxide intermediate layer.

[0008] Furthermore, the step of dissolving polybenzodifuran dione in a mixed solvent containing ethanol and dimethyl sulfoxide includes: Ethanol and dimethyl sulfoxide were mixed at a volume ratio of 8-12:1 to prepare a mixed solvent; Polybenzodifuran diketone was added to the mixed solvent and dispersed under low-frequency ultrasonic conditions of 20-60 kHz for 40-120 min to fully dissolve the polybenzodifuran diketone.

[0009] Furthermore, when preparing the polymer coating solution, multi-walled carbon nanotubes are added to the mixed solvent. The mass ratio of polybenzodifuran diketone to multi-walled carbon nanotubes is 9:1. The composite conductive coating solution is obtained by ultrasonic dispersion. After the composite conductive coating liquid is applied to the surface of the ruthenium-iridium-tantalum ternary oxide intermediate layer, it is first vacuum dried at 100°C, and then placed in a nitrogen atmosphere and cured at 160°C.

[0010] Furthermore, before applying the polymer coating liquid, the surface of the ruthenium-iridium-tantalum ternary oxide intermediate layer is subjected to an interface modification treatment, the interface modification treatment including: A titanium substrate with a ruthenium-iridium-tantalum ternary oxide interlayer is immersed in a 0.8%–1.2% (w / w) solution of 3-aminopropyltriethoxysilane in ethanol, left to stand for 25–35 minutes, then removed and cured at 90–110°C for 8–12 minutes. After cooling, the polymer coating solution is then applied. Furthermore, in the soluble precursor salt containing ruthenium, iridium, and tantalum, the molar ratio of ruthenium, iridium, and tantalum is (1-5):(1-5):(5-9); The coating, pre-baking, and sintering processes were repeated 8 to 16 times to obtain a ruthenium-iridium-tantalum ternary oxide intermediate layer with a thickness of 5 to 10 μm.

[0011] Furthermore, the concentration of polybenzodifuran diketone in the polymer coating solution is 8-12 mg / mL. The coating is repeated twice. After coating, it is first dried in a vacuum environment at 110-130℃ for 50-70 minutes, and then transferred to a nitrogen atmosphere and cured at 170-190℃ for 110-130 minutes.

[0012] Furthermore, the step of first roughening the surface of the titanium substrate by sandblasting and then etching with oxalic acid includes: Sandblasting roughening is performed on the titanium substrate surface using 110-130 mesh white corundum or quartz sand at a pressure of 0.3-0.5 MPa. The oxalic acid etching is performed by immersing the titanium substrate in an oxalic acid solution with a mass fraction of 8% to 15% for 0.5 to 1 hour at a constant temperature of 40 to 60°C. After etching, the material is ultrasonically cleaned with deionized water and then dried at low temperature under nitrogen protection.

[0013] Furthermore, the amount of the polymer coating liquid applied to the surface of the ruthenium-iridium-tantalum ternary oxide intermediate layer is 2–8 g / m².

[0014] The present invention also provides a chlorine-resistant, conductive, and corrosion-resistant composite coating on a titanium substrate surface, comprising a titanium substrate, a ruthenium-iridium-tantalum ternary oxide intermediate layer disposed on the surface of the titanium substrate, and a polybenzodifurandione conductive polymer surface layer disposed on the surface of the ruthenium-iridium-tantalum ternary oxide intermediate layer. The thickness of the ruthenium-iridium-tantalum ternary oxide intermediate layer is 5–10 μm, and the thickness of the surface layer of the polybenzodifurandione conductive polymer is 200–2000 nm.

[0015] Furthermore, the surface layer of the polybenzodifurandione conductive polymer is a composite layer of polybenzodifurandione and multi-walled carbon nanotubes, with a mass ratio of polybenzodifurandione to multi-walled carbon nanotubes of 9:1.

[0016] The method for preparing a chlorine-resistant, conductive, and corrosion-resistant composite coating on a titanium substrate provided in the above embodiments has the following beneficial effects: By setting a conductive polymer surface layer of polybenzodifurandione, the migration and oxidation of organic additive molecules in the solution to the ruthenium-iridium-tantalum ternary oxide intermediate layer are effectively blocked, reducing the ineffective consumption of organic additives on the anode, which helps to maintain the stability of the solution composition and reduce production costs.

[0017] The surface layer can prevent strong oxidizing species generated in chlorine-containing environments from penetrating into the interior of the intermediate layer, slow down the erosion of the active coating, and extend the service life of the composite coating on the titanium substrate surface in chlorine-containing environments.

[0018] The conductive polymer surface layer of polybenzodifurandione has a good bond with the ruthenium-iridium-tantalum ternary oxide intermediate layer, and the thickness of the surface layer is controlled at the nanometer level, which does not affect the electrocatalytic activity of the anode and ensures that the coated electrode can function normally.

[0019] As an n-type conjugated conductive polymer, polybenzodifurandione exhibits superior structural stability in high anodic potential and strongly oxidizing chlorine-containing environments compared to traditional p-type conductive polymers. It is less prone to oxidative degradation during long-term service and can maintain a durable protective effect. Attached Figure Description

[0020] Figure 1 This is a flowchart of a method for preparing a chlorine-resistant, conductive, and corrosion-resistant composite coating on a titanium substrate surface, as provided in an embodiment of the present invention. Figure 2 This is a SEM image of Embodiment 1 in this invention; Figure 3 These are accelerated aging life test diagrams of various embodiments and comparative examples in this invention; Figure 4 This is a test graph showing the oxygen evolution potential and the consumption of electroplating additives in various embodiments and comparative examples of this invention. The realization of the objective, functional features and advantages of the present invention will be further explained in conjunction with the embodiments and with reference to the accompanying drawings. Detailed Implementation

[0021] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.

[0022] Reference Figure 1 This is a schematic flowchart of a method for preparing a chlorine-resistant, conductive, and corrosion-resistant composite coating on a titanium substrate surface, as proposed in this invention, including the following steps: S1. The surface of the titanium substrate is first roughened by sandblasting, then etched with oxalic acid, cleaned and dried for later use. S2, a soluble precursor salt containing ruthenium, iridium, and tantalum is dissolved in an alcohol solvent to obtain a coating solution. The coating solution is then applied to the surface of the titanium substrate. After each coating, the substrate is pre-baked at 130–160°C and then sintered at 550–600°C. This coating, pre-baking, and sintering process is repeated 8–16 times to form a ruthenium-iridium-tantalum ternary oxide intermediate layer with a thickness of 5–10 μm on the surface. The molar ratio of ruthenium, iridium, and tantalum in the soluble precursor salt containing ruthenium, iridium, and tantalum is (1–5):(1–5):(5–9). S3, dissolve polybenzodifuran dione in a mixed solvent containing ethanol and dimethyl sulfoxide to obtain a polymer coating solution; S4, the polymer coating liquid is coated on the surface of the ruthenium-iridium-tantalum ternary oxide intermediate layer, first dried at 80-120°C to remove the solvent, then cured at 160-300°C to form a film, and after cooling, a polybenzodifurandione conductive polymer surface layer with a thickness of 200-2000 nm is formed on the ruthenium-iridium-tantalum ternary oxide intermediate layer.

[0023] As described in step S1 above, the titanium substrate is selected as TA1 grade industrial pure titanium. The surface is first roughened by sandblasting using 110-130 mesh white corundum or quartz sand as the sandblasting medium. The sandblasting pressure is maintained at 0.3-0.5 MPa to create a uniformly rough surface across the entire area to be coated. After sandblasting, the titanium substrate is immersed in an 8%-15% oxalic acid solution at a temperature of 40-60°C for 0.5-1 hour. The oxalic acid etching action creates a micro-rough structure on the surface, while simultaneously removing residual particles and the original oxide film from the sandblasting process. After etching, the titanium substrate is removed and ultrasonically cleaned in deionized water for 5-15 minutes to thoroughly remove any remaining oxalic acid residue and impurities. The cleaned titanium substrate is then dried in a nitrogen-protected environment at a temperature controlled at 60-80°C to prevent oxidation of the fresh surface during drying. After the above treatment, the surface of the titanium substrate should be kept clean, free of oil, oxidation residue, and dust. It should then be transferred to a sealed, dry container for storage and use, providing a clean substrate surface with good adhesion for the uniform coating of the ruthenium-iridium-tantalum ternary oxide intermediate layer.

[0024] As described in step S2 above, after completing the surface pretreatment, soluble precursor salts of ruthenium, iridium, and tantalum are added to an alcohol solvent and stirred continuously until the solute is fully dissolved. After standing, the solution is filtered to remove insoluble impurities, yielding a coating solution. This coating solution is then uniformly coated onto the surface of a titanium substrate using either brushing or dipping. After each coating, the titanium substrate is placed in an oven at 130–160°C for 25–35 minutes to allow the solvent to fully evaporate. Subsequently, it is transferred to a high-temperature sintering furnace at 550–600°C for thermal oxidation for 40–60 minutes, converting the metal salts into the corresponding metal oxides and forming a solid solution. After cooling to room temperature, the coating is repeated. This coating, pre-drying, and sintering cycle is repeated 8–16 times until the ruthenium-iridium-tantalum oxide coating thickness reaches 5–10 μm, thereby forming a uniform and continuous ruthenium-iridium-tantalum ternary oxide intermediate layer on the surface of the titanium substrate.

[0025] As described in step S3 above, when preparing the polymer coating solution, ethanol and dimethyl sulfoxide are mixed evenly at a volume ratio of 8–12:1 to obtain a mixed solvent. Polybenzodifuran diketone is added to this mixed solvent, controlling its concentration to 1–20 mg / mL. Subsequently, it is treated under low-frequency ultrasonic conditions of 20–60 kHz for 40–120 min to ensure the polybenzodifuran diketone is fully dissolved and evenly dispersed, thus obtaining the polymer coating solution. The resulting coating solution can be directly used in the coating process after standing.

[0026] As described in step S4 above, a polymer coating liquid is coated onto the surface of the ruthenium-iridium-tantalum ternary oxide intermediate layer. The coating can be applied by brushing or spraying, ensuring the coating liquid is evenly spread across the entire surface. After coating, the titanium substrate is placed in an oven at 80–120°C for 20–40 minutes to remove the solvent. The dried titanium substrate is then transferred to a sintering furnace and cured at 160–300°C for 30–120 minutes, allowing the polybenzodifuran diketone to form a continuous and dense conductive polymer film on the intermediate layer surface. After cooling to room temperature, the surface condition is checked. The thickness of the resulting polybenzodifuran diketone conductive polymer surface layer is controlled to be 200–2000 nm. This surface layer covers the ruthenium-iridium-tantalum ternary oxide intermediate layer and is tightly bonded to it, serving to prevent chloride ions and organic additive molecules from penetrating into the active coating.

[0027] The present invention will be specifically described below through examples and comparative examples. Example 1

[0028] TA1 grade industrial pure titanium was selected as the titanium substrate. First, 110-130 mesh white corundum was used to roughen the surface of the titanium substrate by sandblasting under a pressure of 0.3-0.5 MPa to form a uniform rough surface. Then, the sandblasted titanium substrate was immersed in an 8%-15% oxalic acid solution and soaked at a constant temperature of 40-60℃ for 0.5-1 h to complete the oxalic acid etching. After etching, the substrate was ultrasonically cleaned with deionized water and dried at low temperature under nitrogen protection for later use.

[0029] A mixed solvent of n-butanol and ethanol was selected, and soluble precursor salts of the corresponding metals were added in a molar ratio of 3:3:7 for ruthenium, iridium and tantalum. The mixture was stirred until the solutes were fully dissolved and allowed to stand. The insoluble impurities were removed by filtration to obtain a ruthenium-iridium-tantalum ternary coating solution.

[0030] The coating solution was applied to the pretreated titanium substrate surface. After each coating, the substrate was pre-baked in an oven at 130–160°C for 25–35 minutes, and then transferred to a high-temperature sintering furnace at 550–600°C for thermal oxidation for 40–60 minutes. After cooling, the coating-pre-baking-sintering operation was repeated for a total of 13 cycles, resulting in a uniform, continuous, and tightly bonded ruthenium-iridium-tantalum ternary oxide intermediate layer with a thickness of approximately 7 μm on the titanium substrate surface.

[0031] Using ethanol as the main solvent and adding a small amount of dimethyl sulfoxide, polybenzodifurandione was added to the mixed solvent and ultrasonically treated under low frequency conditions to fully dissolve the polymer, thus obtaining a polymer coating solution. The polymer coating solution was coated onto the surface of a ruthenium-iridium-tantalum ternary oxide intermediate layer at a coating amount of 4 g / m². It was first baked in an oven at 100°C for 20 minutes, and then cured in a low-temperature furnace at 250°C for 40 minutes. After cooling, a conductive polymer surface layer of polybenzodifurandione with a thickness of 200-500 nm was formed, thus obtaining a titanium-based chlorine-resistant and corrosion-resistant composite coating anode.

[0032] Figure 2 The image shows the surface SEM morphology of the composite coating obtained in Example 1, with a scale bar of 100 μm. As can be seen from the image, the conductive polymer surface layer of polybenzodifuran diketone uniformly covers the surface of the ruthenium-iridium-tantalum ternary oxide intermediate layer. The composite coating is continuous and dense overall, without defects such as through cracks, pinholes, or large-area peeling. The film surface exhibits a natural micro-uneven morphology following the intermediate layer substrate, with only a small number of fine particle protrusions formed during the solution coating and curing process. This complete and dense film structure can effectively physically shield the underlying oxide active layer, preventing chloride ions and organic additive molecules from penetrating into the coating interior. This is the structural basis for achieving both chloride resistance and extended service life, as well as reduced additive consumption. Example 2

[0033] The preparation process of this embodiment is basically the same as that of Example 1, except that the ruthenium-iridium-tantalum ternary oxide intermediate layer is replaced with an iridium-tantalum binary oxide active intermediate layer, Ir:Ta=7:3, and the titanium substrate pretreatment, polybenzodifuran diketone coating solution preparation, coating curing process and parameters are all the same as those of Example 1. Example 3

[0034] This embodiment optimizes the basic process of Example 1. After preparing the ruthenium-iridium-tantalum ternary oxide intermediate layer, the titanium substrate with the intermediate layer is first immersed in a 1% (w / w) solution of 3-aminopropyltriethoxysilane ethanol, left to stand for 30 minutes, and then removed and cured at 100°C for 10 minutes to complete the interface modification treatment.

[0035] A 10 mg / mL polybenzodifurandione polymer coating solution was prepared and coated twice on the surface of the modified intermediate layer. After coating, the coating was dried in a vacuum environment at 120°C for 1 hour, and then cured at 180°C under a nitrogen atmosphere for 2 hours to finally obtain a polybenzodifurandione conductive polymer surface layer with a thickness of about 1-2 μm. The remaining process parameters were the same as in Example 1. Example 4

[0036] The basic process of this embodiment is basically the same as that of Example 1. The difference is that when preparing the polymer coating liquid, polybenzodifuran diketone and multi-walled carbon nanotubes are added to the mixed solvent at the same time. The mass ratio of polybenzodifuran diketone to multi-walled carbon nanotubes is 9:1. The mixture is ultrasonically dispersed for 2 hours to obtain a composite conductive coating liquid. After coating, it is first vacuum dried at 100°C, and then placed under nitrogen protection and kept at 160°C for 1 hour to obtain a composite conductive polymer surface layer with a thickness of 300-800 nm.

[0037] Comparative Example 1 The preparation process of this comparative example is basically the same as that of Example 1, except that: no surface layer of polybenzodifurandione conductive polymer is prepared, and only the ruthenium-iridium-tantalum ternary oxide intermediate layer is retained.

[0038] Comparative Example 2 The preparation process of this comparative example is basically the same as that of Example 1, except that: the intermediate layer uses an iridium-tantalum binary oxide coating and no polybenzodifurandione conductive polymer surface layer is prepared.

[0039] The anode samples prepared in Examples 1-4 and Comparative Examples 1-2 were subjected to accelerated aging lifetime tests, oxygen evolution potential tests, and electroplating additive consumption tests, respectively. The test methods are as follows: A chlorine-containing environment was simulated using a 1 mol / L NaCl electrolyte, with a current density of 500 A / m², a test temperature of 25 ± 2℃, a pure titanium plate as the cathode, and an electrode spacing of 2 cm. The cumulative energizing time when the cell voltage increased by 5V from the initial value was used as the criterion for determining the enhanced lifespan.

[0040] Electrochemical tests were performed in a 1 mol / L H2SO4 electrolyte, with a scanning potential range of 0.4 V to 2.0 V (vs. SCE) and a scanning rate of 20 mV / s. A saturated calomel electrode was used as the reference electrode.

[0041] Under rated power conditions, the system was continuously operated until the cumulative power consumption reached the set value. The concentration of additives in the plating solution before and after the experiment was detected using a CVS electroplating additive concentration tester. The additive consumption per kiloampere-hour was calculated, with the unit being ml / kWh.

[0042] Comparative Example 1, with only a ruthenium-iridium-tantalum ternary oxide interlayer and no polybenzodifurandione conductive polymer surface layer, exhibited a low oxygen evolution potential of 1.243V and excellent electrocatalytic activity. However, its accelerated lifetime was only about 280 hours, and the consumption of electroplating additives was as high as 101 ml / KAH. The problems of chloride ion corrosion of the coating and ineffective anodizing of the additives were particularly prominent. Comparative Example 2, using an iridium-tantalum binary interlayer and no polymer surface layer, had an accelerated lifetime of only about 265 hours, an oxygen evolution potential of 1.265V, and an additive consumption of 103 ml / KAH, making its overall performance the worst among all groups.

[0043] Comparing Example 1 with Comparative Example 1 and Example 2 with Comparative Example 2, it can be seen that after introducing a polybenzodifurandione conductive polymer surface layer on the surface of the oxide intermediate layer, the accelerated life of the anode is significantly improved, while the ineffective consumption of electroplating additives is greatly reduced. This proves that the polymer surface layer can play a dual role in blocking chloride ion corrosion and inhibiting the anodization of organic additives.

[0044] Combination Figure 3 and Figure 4 As shown, Example 1 uses a ruthenium-iridium-tantalum ternary oxide intermediate layer combined with a polybenzodifuran diketone surface layer. The oxygen evolution potential is 1.245V, and the electroplating additive consumption is 75ml / KAH. These two indicators are the best among all examples. At the same time, the accelerated life can reach about 350h. It achieves a balanced optimization of low oxygen evolution energy consumption, low additive consumption and chlorine corrosion resistance life, demonstrating the synergistic effect between the ternary oxide intermediate layer and the polymer surface layer.

[0045] Example 2 uses an iridium-tantalum binary oxide interlayer paired with the same polymer surface layer, accelerating the lifespan to approximately 400 hours, demonstrating that the polybenzodifurandione conductive polymer surface layer can be adapted to oxide interlayers with different compositions. However, compared to Example 1, its oxygen evolution potential increases to 1.267V, and the additive consumption increases to 85ml / KAH, indicating that the ruthenium-iridium-tantalum ternary oxide interlayer has significant advantages in reducing operating energy consumption and additive consumption, and its overall performance is superior.

[0046] Example 3, through silane interface modification and thickening of the polymer surface, further increased the lifespan to approximately 420 hours, the highest among all groups, with an oxygen evolution potential of 1.256V and an additive consumption of 90 ml / KAH, making it suitable for chlorine-containing conditions with higher lifespan requirements.

[0047] Example 4 uses a conductive polymer surface layer composed of polybenzodifuran dione and multi-walled carbon nanotubes, which accelerates the lifespan to about 400 hours, has an oxygen evolution potential of 1.249 V, and consumes 82 ml / KAH of additives. The introduction of carbon nanotubes further improves the conductivity of the polymer surface layer, enabling the scheme to achieve both good electrocatalytic activity and corrosion resistance.

[0048] In summary, this invention achieves comprehensive performance optimization in three dimensions: chlorine corrosion resistance life, oxygen evolution working energy consumption, and inhibition of ineffective consumption of electroplating additives by constructing a polybenzodifurandione conductive polymer surface layer on top of an oxide active intermediate layer. Different embodiments have different focuses in each performance dimension, and can be flexibly selected according to actual application conditions.

[0049] It should be noted that, in this document, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, apparatus, article, or method that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, apparatus, article, or method. Unless otherwise specified, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, apparatus, article, or method that includes that element.

[0050] The above description is only a preferred embodiment of the present invention and does not limit the patent scope of the present invention. Any equivalent structural or procedural transformations made based on the content of the present invention specification and drawings, or direct or indirect applications in other related technical fields, are similarly included within the patent protection scope of the present invention.

Claims

1. A method for preparing a chlorine-resistant, conductive, and corrosion-resistant composite coating on a titanium substrate surface, characterized in that, Includes the following steps: The surface of the titanium substrate is first roughened by sandblasting, then etched with oxalic acid, cleaned and dried for later use. A soluble precursor salt containing ruthenium, iridium, and tantalum is dissolved in an alcohol solvent to obtain a coating solution. The coating solution is then applied to the surface of the titanium substrate. After each coating, the substrate is pre-baked at 130–160°C and then sintered at 550–600°C. This coating, pre-baking, and sintering process is repeated 8–16 times to form a ruthenium-iridium-tantalum ternary oxide intermediate layer with a thickness of 5–10 μm on the surface. The molar ratio of ruthenium, iridium, and tantalum in the soluble precursor salt containing ruthenium, iridium, and tantalum is (1–5):(1–5):(5–9). Polybenzodifuran dione was dissolved in a mixed solvent containing ethanol and dimethyl sulfoxide to obtain a polymer coating solution; The polymer coating liquid is applied to the surface of the ruthenium-iridium-tantalum ternary oxide intermediate layer. The solvent is first removed by drying at 80-120°C, and then cured into a film at 160-300°C. After cooling, a polybenzodifuran diketone conductive polymer surface layer with a thickness of 200-2000 nm is formed on the ruthenium-iridium-tantalum ternary oxide intermediate layer.

2. The method for preparing a chlorine-resistant, conductive, and corrosion-resistant composite coating on a titanium substrate surface according to claim 1, characterized in that, The step of dissolving polybenzodifuran dione in a mixed solvent containing ethanol and dimethyl sulfoxide includes: Ethanol and dimethyl sulfoxide were mixed at a volume ratio of 8-12:1 to prepare a mixed solvent; Polybenzodifuran diketone was added to the mixed solvent and dispersed under low-frequency ultrasonic conditions of 20-60 kHz for 40-120 min to fully dissolve the polybenzodifuran diketone.

3. The method for preparing a chlorine-resistant, conductive, and corrosion-resistant composite coating on a titanium substrate surface according to claim 1, characterized in that, When preparing the polymer coating solution, multi-walled carbon nanotubes are added to the mixed solvent. The mass ratio of polybenzodifuran diketone to multi-walled carbon nanotubes is 9:

1. The composite conductive coating solution is obtained by ultrasonic dispersion. After the composite conductive coating liquid is applied to the surface of the ruthenium-iridium-tantalum ternary oxide intermediate layer, it is first vacuum dried at 100°C, and then placed in a nitrogen atmosphere and cured at 160°C.

4. The method for preparing a chlorine-resistant, conductive, and corrosion-resistant composite coating on a titanium substrate surface according to claim 1, characterized in that, Before applying the polymer coating liquid, the surface of the ruthenium-iridium-tantalum ternary oxide intermediate layer is first subjected to an interface modification treatment, the interface modification treatment including: A titanium substrate with a ruthenium-iridium-tantalum ternary oxide intermediate layer is immersed in a 3-aminopropyltriethoxysilane ethanol solution with a mass fraction of 0.8% to 1.2%, left to stand for 25 to 35 minutes, then removed and heated to cure at 90 to 110°C for 8 to 12 minutes. After cooling, the polymer coating liquid is then applied.

5. The method for preparing a chlorine-resistant, conductive, and corrosion-resistant composite coating on a titanium substrate surface according to claim 1, characterized in that, After each application of the ruthenium-iridium-tantalum ternary oxide coating solution, pre-baking is performed at 130–160°C for 25–35 minutes, followed by thermal oxidation at 550–600°C for 40–60 minutes.

6. The method for preparing a chlorine-resistant, conductive, and corrosion-resistant composite coating on a titanium substrate surface according to claim 1, characterized in that, The concentration of polybenzodifuran diketone in the polymer coating solution is 8-12 mg / mL. The coating is repeated twice. After coating, it is first dried in a vacuum environment at 110-130℃ for 50-70 minutes, and then transferred to a nitrogen atmosphere and cured at 170-190℃ for 110-130 minutes.

7. The method for preparing a chlorine-resistant, conductive, and corrosion-resistant composite coating on a titanium substrate surface according to claim 1, characterized in that, The steps of first roughening the surface of the titanium substrate by sandblasting and then etching with oxalic acid include: Sandblasting roughening is performed on the titanium substrate surface using 110-130 mesh white corundum or quartz sand at a pressure of 0.3-0.5 MPa. The oxalic acid etching is performed by immersing the titanium substrate in an oxalic acid solution with a mass fraction of 8% to 15% for 0.5 to 1 hour at a constant temperature of 40 to 60°C. After etching, the material is ultrasonically cleaned with deionized water and then dried at low temperature under nitrogen protection.

8. The method for preparing a chlorine-resistant, conductive, and corrosion-resistant composite coating on a titanium substrate surface according to claim 1, characterized in that, The amount of the polymer coating liquid applied to the surface of the ruthenium-iridium-tantalum ternary oxide intermediate layer is 2–8 g / m².

9. A chlorine-resistant, conductive, and corrosion-resistant composite coating for a titanium substrate, characterized in that, It is composed of a titanium substrate, a ruthenium-iridium-tantalum ternary oxide intermediate layer disposed on the surface of the titanium substrate, and a polybenzodifurandione conductive polymer surface layer disposed on the surface of the ruthenium-iridium-tantalum ternary oxide intermediate layer. The thickness of the ruthenium-iridium-tantalum ternary oxide intermediate layer is 5–10 μm, and the thickness of the surface layer of the polybenzodifurandione conductive polymer is 200–2000 nm.

10. The chlorine-resistant, conductive, and corrosion-resistant composite coating on the titanium substrate surface according to claim 9, characterized in that, The conductive polymer surface layer of the polybenzodifurandione is a composite layer of polybenzodifurandione and multi-walled carbon nanotubes, with a mass ratio of polybenzodifurandione to multi-walled carbon nanotubes of 9:1.